Chronicle of a Soil Bacterium: Paenibacillus polymyxa E681 as a Tiny Guardian of Plant and Human Health - Jeong, Haeyoung; Choi, Soo-Keun; Ryu, Choong-Min; Park, Seung-Hwan (Frontiers in Microbiology, 2019)
The Gram-positive rhizosphere bacterium Paenibacillus polymyxa promotes plant growth and produces various antibiotics. Herein, we review research on this species over the past two and a half decades, and focus on the mechanisms of P. polymyxa strain E681, isolated from barley roots in the Republic of Korea in 1995. Strain E681 has outstanding growth-promoting effects on barley, cucumber, pepper, sesame, and Arabidopsis thaliana and produces antimicrobial compounds that protect plants against pathogenic fungi, oomycetes, and bacteria. Induced systemic resistance elicited by treating seeds or roots with strain E681 is a possible mechanism for protecting systemic plant tissues from biotic and other environmental stresses. Genome sequencing has broadened our horizons for antibiotic development and other industrial applications beyond agricultural use. At least six gene clusters for the biosynthesis of antibiotics have been discovered, including polymyxin (pmx), which was recently re-instated as an antibiotic of last resort against Gram-negative drug-resistant bacteria. Three groups of antibiotic synthetases include the gene clusters that encode one for the nonribosomal peptide polymyxin, fusaricidin, and tridecaptin, another for the lantibiotic paenilan, and the third for a polyketide. We successfully introduced the pmx gene cluster into the surrogate host Bacillus subtilis and created polymyxin derivatives by domain swapping. Furthermore, various E681 derivatives, including a high fusaricidin producer and strains lacking multi-antibiotics production, have been constructed by random mutagenesis and genome engineering. Thus, E681 is an important bacterium that contributes to both plant and human health.